Dynamika zmian na rynku szkolnictwa wyższego a konkurencyjność absolwentów szkół wyższych na rynku pracy - Stosik, Aneta; Kocyłowska, Paulina (Dynamics of changes on the higher education market and graduates' competitiveness on the job market, 2006)
The above article presents the analysis of changes on the higher education market in Poland and presents the research results on graduates' competitiveness on the job market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 170-176